v.1 - "Nigam, Raj K. (ed.)" (New Delhi, 1993)
In Pursuance of a decision of the Board of Directors of the Documentation Centre, a publication entitled TRAUMA OF PUBLIC SECTOR MANAGEMENTS, jointly edited by Dr.S.M. Patil, Major General S.C.N Jatar band me was brought out as a DC PUBLICATION in September 1992.While Work on the new projects was in progress in right earnest, I received , quite unexpectedly, a suggestion from several Chief Executives of public Sector Enterprises, who were encounting immense difficulties in obtaining details Of GovernmentPolicies concerning PSEs a well as official reports and documents , to bring out a publication covering developments having a direct bearing on working of public sector management from 1984 onwards which have till now not been recorded in any book, official or otherwise.
Keywords: Public enterprises 1993